Efficient computation of surface fields excited on a dielectric-coated circular cylinder. - Erturk, V. (IEEE Transactions on antennas and propagation)
An efficient method to evaluate the surface fields excited on an electrically large dielectric-coated circular cylinder is presented. The efficiency of the method results from the circumferentially propagating representation of the Green's function as well as its efficient numerical evaluation along a steepest descent path. The circumferentially propagating series representation of the appropriate Green's function is obtained from its radially propagating counterpart via Watson's transformation and then the path of integration is deformed to the steepest descent path on which the integrand decays most rapidly. Numerical results are presented that indicate that the representations obtained here are very efficient and valid even for arbitrary small separations of the source and field points. This work is especially useful in the moment-method analysis of conformal microstrip antennas where the mutual coupling effects are important